(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to the analysis of the function of artistic detail as a microstructural element in the prose of Sergei Dovlatov. Using key works by the author – particularly the cycles The Suitcase and The Compromise – the study explores how secondary descriptive elements acquire significant semantic weight, shaping the reader’s perception of characters, atmosphere, and narrative dynamics. The research draws on structuralist and narratological methods, as well as on theoretical approaches developed by Mikhail Bakhtin, Yevgeny Dobin, and Viktor Shklovsky regarding the role of detail in literary texts. The study demonstrates that in Dovlatov’s prose, artistic detail functions not only as a means of realistic depiction but also as a vehicle for irony, ambiguity, and the author’s evaluative stance. These semantic microstructures contribute to the polyphonic nature of Dovlatov’s artistic world and foster a unique dialogic connection between narrator and reader. The findings are of interest to specialists in Russian literature, narratology, and literary stylistics.